Anticorrosive Copper Current Collector Passivated by Self‐Assembled Porous Membrane for Highly Stable Lithium Metal Batteries. (29th July 2021) - Wen, Zuxin; Fang, Wenqiang; Chen, Long; Guo, Ziwei; Zhang, Ning; Liu, Xiaohe; Chen, Gen
Abstract: The regulation of lithium plating/stripping behavior is considered to be critical for next‐generation safe and high‐energy‐density lithium metal batteries. Lithium deposition with maximum granular size and minimum microstructural tortuosity can significantly improve the lithium plating/stripping efficiency. Here, a self‐assembled organosilane layer with nanopores is constructed on Cu current collector surface via a thiol‐Cu reaction. In contrast to typical stacked‐particle morphology with small grain size and high specific area in ether electrolyte, dough‐like and lateral‐growth lithium deposition can be plated on the modified Cu current collector due to the low surface energy of a lithiophilic SiOSi membrane. The planar and dense lithium deposition contributes to the stable implementation of up to near 500 cycles in full cells with high‐loading LiFePO4 cathode. Anticorrosion in rigorous Cl‐ion containing solution can even be achieved due to the corrosive repellency of hydrophobic organosilane. A high Coulombic efficiency (97.12%) is remained after corroding for 300 min. Moreover, the irreversible capacity loss caused by galvanic corrosion, an ignored but crucial aspect, has been significantly suppressed due to the passivation of high‐redox‐potential Cu by organosilane coating. Abstract : The self‐assembled porous membrane is constructed on a copper (Cu) current collector via a thiol‐Cu reaction. Dough‐like and lateral‐growth lithium deposition can be plated on the modified Cu, enhancing the electrochemical performance significantly. Moreover, the ability to restrain ambient chlorine ion corrosion and galvanic corrosion, which causes irreversible capacity loss, can be granted due to the passivation of Cu by the membrane.